Physical and Chemical Treatability Assessment for Food Industry Wastewater in Wastewater Treatment Plant Design - Wiharyanto Oktiawan; Junaidi Junaidi; Fadhila Raziani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Food industry wastewater has characteristics that contain high organic matter and suspended solids. Most of the methods used are physical and chemical treatment because these methods have high efficiency and effectivity. In designing a new wastewater treatment plant, the treatability assessment is essential to any consideration or reference in planning the treatment process to be implemented. This research aims to obtain treatability assessment results that will be used as consideration in planning treatment units in WWTP according to the characteristics of wastewater tested. The removal results of the sedimentation test with Imhoff Cone were able to remove 51.2% COD, 64.04% BOD, and 95.21% TSS with the optimum settling time of 40 minutes. The samples test continued to the rapid-slow mixing test using the jar test, resulting that by adding coagulant at the optimum dose of PAC 120 mg/L, it was capable to remove 68.21% of COD, 73.22% of BOD, and up to 98.07% of TSS at the end of the process. Based on the assessment results, the physical and chemical treatment can remove suspended solids pollutant parameters with high efficiency so it will be considered to be used in planning Wastewater Treatment Plants for this food industry.